A facilities manager's typology of performance gaps in new buildings. Issue 1 (21st January 2020) - Rasmussen, Helle Lohmann; Jensen, Per Anker
Abstract : Purpose: The gap between the expected and actual performance of newly built facilities has been widely described in the literature as "the performance gap". Mostly, the performance gap appears to be synonymous with the energy performance gap. Little attention has been given to other performance aspects that facilities managers recognise as deficient in newly built or renovated buildings like for instance difficulties in operation and maintenance. This study contributes with a typology of performance gaps, with the aim to offer a more nuanced understanding of the term, where the interests of facilities management are in focus. Design/methodology/approach: The empirical data consist of four in-depth interviews, two focus group interviews and three workshops. Except for one workshop, the data collection took place in Denmark. Findings: The study identifies 12 types of performance gaps of which "higher energy consumption" is one. The gaps are interdependent and initiatives to reduce one type of gap can potentially lead to an increase in another. Furthermore, the study finds that the fatal (the most critical) gap is context-specific. Research limitations/implications: The findings of this study imply a need to change the way we previously have discussed the early involvement of the facilities management in design. The study shows that more involvement of FM is not necessarily better. Originality/value: This paper is the first attempt to cover performance gaps of buildings from a holistic viewpoint and from the perspective of FM.